Infiltración transtimpánica de corticoides para el tratamiento de los acúfenos subjetivos en pacientes del Hospital de Clínicas de Julio-Agosto 2021 - Serrano-Andrade, Ricardo; Mena Canata, Carlos; Liu , Ta Ju; Tornaco-Maidana, Raúl (Medicina Clínica y Social, 2022)
Introduction: Tinnitus is a problem that affects an important part of the population, whose causes are not entirely clear. Currently there is no cure or consensus on the treatment of tinnitus, which is ineffective in many cases, is accompanied by significant side effects or does not provide symptomatic relief to patients. Intratympanic injection of corticosteroids has been reported to improve symptoms. Objective: to determine the result of transtympanic infiltration of corticosteroids for the treatment of subjective tinnitus. Methods: The design of the study is observational, descriptive and correlational, sampling was non-probabilistic of consecutive cases. Adult patients with unilateral or bilateral tinnitus of more than one month of evolution as the main symptom were included. Results: 25 patients were included in the research, most of them were male with a mean age of approximately 45 years. The main type of hearing loss associated with these patients was sensorineural. No audiometric differences were found between pre and post infiltration. Conclusion: A large percentage of patients had a high degree of disability due to tinnitus and moderate to severe symptoms prior to treatment, after which this decreased, but not significantly.
Keywords: corticosteroids; Injection; dexamethasone; tinnitus